Enhancement or Suppression of ACE Inhibitory Activity by a Mixture of Tea and Foods for Specified Health Uses (FOSHU) That Are Marketed as "Support for Normal Blood Pressure". (4th August 2011) - Murakami, Isao; Hosono, Hiroyuki; Suzuki, Shigeto; Kurihara, Junichi; Itagaki, Fumio; Watanabe, Machiko
Abstract : The ACE inhibitory activities of mixtures of FOSHUs ( Healthya, Goma-Mugicha, Lapis Support and Ameal ) were examined in order to identify any antihypertensive interactions. Among combinations of Healthya with other samples that contain active peptides, only that with Ameal was found to have no inhibitory activity. Enhanced activity was observed in 2 other mixtures. The activity of a mixture of tea polyphenols and the whey component extracted from an Ameal solution was significantly decreased, thus demonstrating that whey protein lowered the ACE inhibitory activity of Healthya . Although oral administration of tea polyphenols alone significantly decreased SBP in SHR at 2 and 4 hr, combined administration with Ameal failed to decrease SBP at the same time points. In conclusion, the simultaneous intake of tea and FOSHUs that contain active peptides might affect daily self-antihypertensive management via enhancement or suppression of ACE inhibitory activity.